At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Our Q&A platform offers a seamless experience for finding reliable answers from experts in various disciplines. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Answer:
Let us assume the two numbers be x and y
From the above condition we can write, x + y = 26 equation 1
second condition first no x = 2 more 5 times of the second no. that is 5y + 2
then we can write, x = 5y + 2..... eqation (2)
from equation 1 x + y = 26
subtracting y from each side , x+ y - y = 26 - y
x = 26 - y
plugging this value of x in eqn. no (2 ) we get,
26-y = 5y + 2
subtracting 5y on both sides,
26 - y - 5y = 5y - 5y + 2
26 - 6y = 2
subtracting 26 from both sides,
26 -26 -6y = 2- 26
-6y = -24
eliminating minus sign from both sides,
6y = 24
dividing by 6 on both sides,
y = 24/6 = 4
substituting this value of y in equation 1 we get,
x + 4 = 26
subtracting 4 from both sides,
x = 26- 4 = 22
Step-by-step explanation:
so we solve the 2 eqns we get x = 22 and y = 4
the two numbers will be 22 and 4
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.